53‐3: Worldwide First Real Border‐less and High Resolution Micro‐LED Display. Issue 1 (28th June 2022) - Kang, Tin; Ke, Tsung-Ying; Huang, Zih-Shuo; Hsieh, Kun-Long; Lin, Yu-Ling; Chen, Fu-Jung; Li, Yi-Shao; Chen, Wei-Chih; Hsieh, Chia-Ting; Wang, Hsiu-Hua; Liu, Chan-Jui; Lin, Wei-Ting; et al.
Abstract : A flexible PI‐less micro‐LED display, 228 PPI, has been achieved by transferring the display devices from rigid glass to plastic. By forming this micro‐LED display on a mold with round edge and lowering the edge radius to 100um, a more cubic waterfall display is realized.